The Evaluation of Diagnostic Role of Cardiac Troponin T (cTnT) in Newborns with Heart Defects - Agata Tarkowska; Wanda Furmaga-Jablonska (The Scientific World Journal)
Heart diseases are a significant cause of morbidity and mortality in newborns. Diagnostic methods are often not sufficient or, in many cases, cannot be used. There is a great advance in medical knowledge concerning biomarkers in the diagnosis of circulatory system in adult patients. Among them, cardiac troponins play the main role. In current literature, there is not enough data concerning the possibility of using them in neonatal cardiac diagnostics. Aim of the Study. To evaluate diagnostic usefulness of cTnT in correlation with other markers of circulatory failure and myocardial damage in newborns with heart defects. Patients and Methods. The study involved 83 newborns up to 46 weeks of postmenstrual age. The exclusion criteria were severe perinatal asphyxia and presence of severe noncardiac diseases. Patients were divided into 2 main groups: group I—54 patients with congenital heart defects (CHDs), and group II (control)—29 healthy neonates. All patients underwent detailed examination of circulatory system. Cardiac troponin T (cTnT) concentrations were evaluated by Roche CARDIAC T Quantitive test. Results. Performed studies revealed that cTnT levels in newborns with heart pathology were significantly higher than in healthy ones. However, cTnT concentrations in patients with CHD did not correlate with clinical symptoms of heart failure, nor with echocardiographic markers of LV function. Type of heart defect did not influence cTnT levels as well. Only hemodynamic significance evaluated by echocardiography influenced the cTnT levels with statistical significance. Conclusions. (1) Statistically significant differences in cTnT levels between newborns with heart defects and healthy subjects were shown. (2) CTnT levels in newborns with heart defects refer only to hemodynamic significance of the defect.